Popular financial report for the city of Los Angeles 2022 - Sambrin Ahmed; Claudia Greco; Marika Lisoni (European Journal of Volunteering and Community-Based Projects)
This report analyzes different financial, economical and social aspects regarding the city of Los Angeles useful to take a broad look at the city to file a Popular Financial Report.